TINDAK PIDANA PENGANIAYAAN DIRENCANAKAN LEBIH DAHULU MENGAKIBATKAN KEMATIAN - Rafli Andhika Wirananda; Fachri Bey (Reformasi Hukum Trisakti, 2022)
The defendant felt sorry for the victim in this case because the defendant had known for 4 (four) years and 4 months that the victim had a relationship with the defendant's wife. As in this case, the defendant stabbed the victim one time at 15.00 WITA while committing the crime of persecution that was premeditated to result in death. According to the analysis and discussion conducted by the researchers, the defendant in this case should have been charged with violating Article 353, paragraph 3 of the Criminal Code, which relates to the events in Case Number 15/Pid.B/2021/PN. Bit. The issue is how the punishment for the persecutors of the crime of persecution was planned in advance, leading to the death of Case Number 15/Pid.B/2021/PN. Beets, and whether the perpetrator's actions satisfy the primary indictment under Article 338 of the Criminal Code. The research approach utilized is normative legal research, which has the characteristics of descriptive research and is qualitatively assessed with the use of secondary sources. The study's findings, analysis, and conclusion show that Jondry Kansil's acts satisfied every requirement of Article 353(3) of the Criminal Code, and the offender was sentenced under the combined sentencing theory.